Pengaruh Kualitas Layanan terhadap Kepuasan Nasabah Mobile Banking pada Bank Pembangunan Daerah Provinsi Sumatera Barat - Jhon Fernos; Gwen Gietricen (JURNAL PUNDI, 2019)
This study aims to analyze the effect of reliability, responsiveness, assurance (assurance), empathy (empathy) and direct evidence (tangibles) on satisfaction of mobile banking customers at the Regional Development Bank of West Sumatra Province. The research design is correlational. The population in this study were all Sharia banking customers in Surakarta City, a sample of 100 mobile banking customers at the Regional Development Bank of West Sumatra Province with a proportion of rendom sampling as a sampling technique. Data analysis in this  study used multiple linear regression (multiple regression analysis). The results showed that there was no tangible variable effect (X1) on customer satisfaction of the Regional Development Bank of West Sumatra Province. No effect on reliability variable (X2) on customer satisfaction of the Regional Development Bank of West Sumatra Province. There is no effect on the responsiveness variable (X3) on customer satisfaction. There is the effect of assurance variable (X4) on customer satisfaction. There is the influence of the empathy variable (X5) on customer satisfaction.